A 2006 Social Accounting Matrix for Rwanda - Diao, Xinshen (International Food Policy Research Institute, 2012)
The 2006 Social Accounting Matrix (SAM) for Rwanda represents the structure of Rwandan economy and the links among various production activities, income distribution, household consumption of goods and services, savings and investments, and foreign trade for the year 2006. This SAM has been modified from the o riginal SAM, which was constructed by Arnault Emini (2007) under a joint project between the Ministry or Economy and Finance (MINECOFIN) in collaboration with the Ministry of Agriculture (MINAGRI) and the World Bank. In this SAM, the three main components of Rwandan economy: (i) agriculture, (ii) industry, and (iii) services are disaggregated into 53 sectors. The agriculture sector includes 16 crops, 7 livestock, 1 fishery and 1 forestry sub-sector. The industry sector comprises 13 manufacturing, 1 mining, and 1 construction, and 1 electricity, gas and water subsector. Similarly, the service sector consists of 9 private and 3 public service subsectors. The 2006 SAM data files comprises of two worksheets; one for the SAM data and the other containing legend to the SAM data. The value for each entry is reported in million Rwandan francs (2006 prices). The data used for building this SAM was obtained from various sources including National Institutes of Statistics of Rwanda, Rwandan Revenue Authority, National Bank of Rwanda, and 2005-2006 Household Living Conditions Survey.